DEVELOPMENT OF STRENGTH ENDURANCE QUALITIES AMONG STUDENTS - Irmatov Shavkat Anvarovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
The article describes the features of the development of power endurance in athletes of various sports (using the example of powerlifting, weightlifting, weight lifting). Strength endurance is defined as the ability to overcome or counter a certain resistance through muscle activity (muscle effort).